Supply Chain Management and Optimization in Manufacturing - Pirim, Harun; Al-Turki, Umar; Yilbas, Bekir Sami (Manufacturing and Surface Engineering, 2014)
This book introduces general supply chain terminology particularly for novice readers, state of the art supply chain management and optimization issues and problems in manufacturing. The book provides insights for making supply chain decisions, planning and scheduling through supply chain network. It introduces optimization problems, i.e. transportation of raw materials, products and location, inventory of plants, warehouses and retailers, faced throughout the supply chain network.